Feelings and experiences of counseling practicum students and implications for counseling supervision - Mansor, Norwati; Wan Yusoff, Wan Mazwati (MCSER Publishing, 2013)
This study focuses on Counseling Practicum students’ feelings and experiences during the Bachelor in Education program at International Islamic University. The students, who were in Guidance and Counseling specialization, had to go through two phases of training; practicum for seven weeks and internship for fourteen weeks. These training periods provide them an opportunity to apply related theories and techniques that they had learnt during three to four years of their studies. The participants for this study consisted of ten third year students from Guidance and Counseling course. This qualitative research adopted students’ journals, group counseling supervision, documentations, case presentation and interviews as the data resources to reveal rich description of the students’ feelings and experiences. The findings indicate five main themes derived for discussion which include nervousness, ability and counseling skills, negotiating students’ or clients’ perceptions, lack of confidence in application of theories, and task completion. Further, this study provides an insight for supervisors to highlight issues and challenges in assisting future trainee counselors